Development and Validation of a Qur’an-Based Prophetic Intelligence Scale: Evidence from Confirmatory Factor Analysis - Khalid, Husain; Malay, M. Nursalim; Isnaini, Nurul (Jurnal Psikologi Islam dan Budaya, 2026)
Globalization impacts learning, yet modern education often overemphasizes cognitive intelligence, neglecting other dimensions and risking a generational moral crisis. This highlights the need for comprehensive intelligence frameworks. This study developed and validated a Quran-based prophetic intelligence instrument based on Abdul Aziem’s framework, comprising six dimensions: spiritual, emotional, intellectual, adversity, physical, and naturalistic intelligence. Data from 437 respondents (aged 20–60) were collected via purposive sampling. The development involved literature reviews, expert judgments (psychologists and Islamic scholars), and psychometric evaluation using Confirmatory Factor Analysis (CFA). Results indicated composite reliability ranging from 0.71 to 0.86, with the higher-order construct showing excellent reliability (CR = 0.99). The model achieved acceptable fit (RMSEA = 0.081; TLI = 0.99; CFI = 0.99; SRMR = 0.03). Ultimately, 35 of the 52 initial items were retained. The findings confirm that the instrument is a valid and reliable measure of prophetic intelligence.